The Wonderful World of Oz - Fricke, John (Down East Books,U.S., 2013)
The wonderful world of Oz is a magical place-and has been for generations of Americans since L. Frank Baum penned his enduring classic in 1900. With the 1939 movie starring Judy Garland, Oz was forever woven into our culture. Over the course of the 20th century, Oz continued to capture the hearts of the American people-as well as people all over the world. This book documents that magical journey through beautiful photographs of the world's largest collection of Oz memorabilia. Whether it's first-edition covers, a munchkin costume, or the Wicked playbill, the iconic items on these pages tell the story of America's most beloved fairy tale. Come over the rainbow and see why there truly is no place like Oz. The wonderful world of Oz is a magical place-and has been for generations of Americans since L. Frank Baum penned his enduring classic in 1900. With the 1939 movie starring Judy Garland, Oz was forever woven into our culture. Over the course of the 20th century, Oz continued to capture the hearts of the American people-as well as people all over the world. This book documents that magical journey through beautiful photographs of the world's largest collection of Oz memorabilia. Whether it's first-edition covers, a munchkin costume, or the Wicked playbill, the iconic items on these pages tell the story of America's most beloved fairy tale. Come over the rainbow and see why there truly is no place like Oz
Keywords: Baum; L. Frank; Wizard of Oz; Children's stories; American; Fantasy fiction; American; Children; Oz (Imaginary place)